Characterization of aerobic granular sludge developed under variable and low organic loading rate - Nik Azimatolakma Awang,; Md Ghazaly Shaaban,; Lee, Choon Weng; Bong, Chui Wei (Penerbit Universiti Kebangsaan Malaysia, 2017)
Understanding the formation of aerobic granules sludge (AGS) under the variations of organic loading rate (OLR) could give a different insight on AGS stability, which had become the bottleneck for practical application in sewage treatment. This study demonstrates the formation of AGS that had previously been stored for eight months at 5ºC in sequencing batch reactor (SBR) with sewage as substrate. Despite being redeveloped under variable OLR of 0.26 to 0.81 kg CODs/m3 d and low superficial air velocity (SAV) of 1.33 cm/s, the loose structure of AGS during storage can be recovered within 46 days of formation process. Variations in OLR intrude the formation process particularly during low OLR, resulting in longer period to achieve mature AGS or full granulation of biomass in reactor. The next-generation sequencing (NGS) analysis indicated that the shift in microbial community from Rhodocyclaceae to Comamonadaceae class for denitrification process was accommodated with the changes in the AGS size from 326 μm to more than 600 μm.